Egg laying behavior of Aedes aegypti and Aedes albopictus mosquitoes in various containers in Gampong Kopelma Darussalam, Syiah Kuala District - Athaillah, Farida; Riandi, Lian Varis; Winaruddin, Winaruddin; Zainuddin, Zainuddin; Usrina, Nora; Putri, Rahmi Eka (The International Journal of Tropical Veterinary and Biomedical Research, 2024)
This study aims to determine the influence of egg laying behavior on containers on the density of Aedes aegypti and Aedes albopictus mosquito larvae in Gampong Kopelma Darussalam, Syiah Kuala District. Sampling was conducted using a simple random sampling technique by surveying larvae in containers from 100 houses. This was followed by the identification of mosquito larval species, and the data were analyzed using entomological indices and Chi-Square tests. Based on the calculation of the entomological index in Gampong Kopelma Darussalam, Syiah Kuala District obtained the values of the House Index, Container Index, and Breteau Index for containers outside the house are 15%, 28.3%, and 17% and the values of House Index, Container Index and Breteau Index for containers in the house are 26%, 13.1%, and 29% so that it can be categorized that the density of Aedes aegypti and Aedes albopictus mosquito larvae in Gampong Kopelma Darussalam, Syiah Kuala District is moderate. The results showed that Aedes aegypti was found to be more than 85.1% compared to Aedes albopictus 14.9%. The analysis results showed a relationship between the type, location, material, size, and color of the container with the presence of Aedes aegypti mosquito larvae in contrast to Aedes albopictus mosquito larvae which showed a relationship with the type, location, and material of the container. The results indicated that Aedes aegypti mosquito larvae were predominantly found in containers inside the house, whereas Aedes albopictus mosquito larvae were more frequently found in containers outside the house.